IKLAN ROKOK A MILD: SUATU TINJAUAN SEMIOTIK - MUHARDIS S.S, MUHARDIS (STKIP PGRI Sumatera Barat, 2010)
The object of this research is cigarette advertising of Sampoerna A Mild versioninannimated object. It’s intent on to explain meaning which used by sign. To analysis this signused semiotic theory by Saussure. The first step, find relation between signifier and signified.The second ones, gave meaning. The result, all of sign have one meaning that is to say quality ofSampoerna A Mild.Keyword: